2018
DOI: 10.12962/j23373520.v7i1.28692
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Deskriptif Pengguna Kosmetik Aktif di Surabaya

Abstract: Pertumbuhan Industri Kosmetik Indonesia bertumbuh secara positif setiap tahunnya. Tujuan dari penelitian ini adalah mengidentifikasi karakteristik demografis pengguna kosmetik merek asing. Penelitian ini menggunakan pendekatan deskriptif-konklusif dengan menggunakan pengumpulan data yang bersifat multi cross-sectional. Data penelitian ini diperoleh menggunakan survei kuesioner yang disebar di Surabaya dan menghasilkan 473 responden pengguna kosmetik aktif yang pernah menggunakan kosmetik merek asing. Hasil dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
2
2
0
1
Order By: Relevance
“…Based on the results of the study, it was found that face powder and lipstick products were the most-used and the most-purchased cosmetic category by consumers with a percentage of 72% in face powder products and 70% in lipstick products. This result was in line with three research findings as described below [11,16,20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the results of the study, it was found that face powder and lipstick products were the most-used and the most-purchased cosmetic category by consumers with a percentage of 72% in face powder products and 70% in lipstick products. This result was in line with three research findings as described below [11,16,20].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, the psychological motives that make cosmetic consumers switched brands were curiosity, variety-seeking, and need for novelty. This result was also in line with a study conducted by Navitasari, Gunawan, and Persada in 2018, of which 38.90% cosmetic consumers in Surabaya were also found to performed brand switching when they felt incompatible with the previous brand [20].…”
Section: Post-purchase Behavior: Brand Switching and Multibrand Loyaltysupporting
confidence: 91%
“…The results of the age frequency distribution of respondents in this study were 68% aged 17-25 years. Where this age is the age range of late adolescence and technology and cosmetic trends are developing a lot among teenagers [5].…”
Section: Data Collectionmentioning
confidence: 99%
“…From these results, 11% of respondents used a facial wash product with the Ms.Glow brand (Figure 1). Brands have a very important role in the consumer decision-making process [5] Ms Glow is a very famous brand in Indonesia. In addition to prioritizing consumer comfort, the company is very concerned about the safety and quality of the ingredients used in MS Glow products, this is evidenced by the existence of halal certification and certification on MS Glow products so that they can attract consumers to use these products [7].…”
Section: Respondent Demographic Datamentioning
confidence: 99%
“…Kurangnya pengetahuan akan bahaya penggunaan pemutih kulit wajah yang berlebihan dan ketidaktahuan bahanbahan yang digunakan sebagai pembuat pemutih kulit wajah ini, menjadikan pemutih kulit wajah masih sebagai kebutuhan yang harus dipenuhi. (7) Penelitian ini sejalan dengan penelitian Syam (2017) yang menunjukkan bahwa pada range umur antara 17-22 tahun yang memakai krim pemutih sebanyak 32 orang (35.56%) dan 23-55 tahun sebanyak 58 orang (64.44%). Dari range umur tersebut yang paling banyak menggunakan krim pemutih range umur antara 23 -55 tahun.…”
Section: Pembahasanunclassified